Enhancing methods engineering education with a digital platform: usability and educational impact on industrial engineering students - Escobar-Castillejos, David; Sigüenza-Noriega, Iñaki; Noguez, Julieta; Escobar-Castillejos, Daisy; Berumen-Glinz, Lorena Alexandra (Frontiers in Education, 2024)
Introduction: Work study aims to comprehend the potential of human work by assessing the duration of tasks and identifying methods for reducing them to enhance productivity and efficiency.On the other hand, methods engineering analyzes job processes to determine the most efficient and cost-effective techniques, resulting in improved operations. These areas are essential in the field of industrial engineering. Traditionally, they are taught using printed manuals and classroombased instruction. Nevertheless, these conventional strategies frequently encounter difficulties engaging students and generating solid comprehension of the topics. Methods: This study involved the development of a digital platform to improve methods engineering education. The platform adapts the curriculum of the methods engineering course offered at Universidad Panamericana. Each laboratory's practice includes detailed instructions and tasks for students to complete. Upon finishing, students submit their reports, which the professor then assesses. If the report meets the required standards, it is approved; otherwise, students must repeat the activities. An experience system serves as a tracker for course completion and keeps track of the student's progress. Results: An experimental group of 26 students who responded to Doll and Torkzadeh's end-user computer satisfaction survey tested the platform. Participants responded positively, particularly regarding the platform’s accuracy (73.08% high satisfaction), ease of use (majority rated 5 for user-friendliness), and timeliness (majority satisfied with up-to-date information). However, the format dimension received mixed ratings, indicating areas for improvement. Additionally, participants appreciated the platform’s ability to track progress and motivate the completion of laboratories, with 61.54% finding the content relevant and valuable for learning methods engineering concepts. Discussion: The results suggest that integrating digital platforms into educational settings could significantly enhance educational settings, particularly in engineering courses where conventional approaches struggle to maintain student interest and engagement. Participants' positive responses support digital platforms' potential to complement and improve teaching methods. Future research will focus on integrating adaptive learning and generating micro-credentials to certify student expertise.